ANALYSIS ARMS RACE BETWEEN THE US AND CHINA OF USING THE MODEL RICHARDSON - Мосора, М. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The possibility of modeling of international relations, taking into account their dynamic properties was explored. We recognize the mathematical model simplified view of the world and emphasize its limited properties. Structural and logical schema of Richardson models of its constituent elements was drawn. The use of the model to predict the foreign policy of the US-China relationship was grounded. The trend possible opposition was analyzed on the basis of the values of factors: the military threat, burden, past images. The level of militarization of the economy through the prism of expenditures on military industry was exposed. The level of complexity of spending on defense budgets was explored. The attention was focused on the basic contradiction between the two countries in the XXI century. The analysis of the results and set the level of the arms race on the basis of stability was shown. The current condition of international relations (US-Chinese vector) were studied.